RUQYAH DALAM PERSPEKTIF TAFSIR ISYARI: TELAAH PENAFSIRAN IMAM AL-ALUSI DALAM KITAB RUH AL-MA’ANI - Yuliana Dethan; Septiawadi; Masruchin (CV. Doki Course and Training, 2023)
This study aims to find out the interpretation of the Ruqyah verse, so that it is not misused in interpreting Ruqyah as found in the isyari interpretation. Because many mistakes occur in the treatment of Ruqyah so that they fall into shirk and believe in the existence of a jinn in one's body. Using a descriptive analysis method through the literature with a tasawuf approach and linguistic semantics to find out the meaning of Ruqyah. Based on the results of the research, it was found that the interpretation of the Ruqyah verse can be seen in the syifā' pronunciation, namely: QS. Yunus 10:57, QS. Al-Isrā’ [17]: 82, QS. Fusilat [41]: 44, QS. Asy-Syu'ara [26]: 80, QS. At-Taubah [9]: 14, where these five letters form the basis for the stages of healing in Ruqyah including the first; ma'rifatullah, beginning with tazkiyatun nafs, self-purification from evil and sin by repenting with mau'iẓah, and filling it with commendable morals. The two Ruqyah are independent by reading the Qur'an, isti'azah and the third is Ruqyah by experts.